Effectiveness of Data Preprocessing for Data Mining (International Journal of Current Engineering and Technology, 2014)
Data Preprocessing is the most crucial step as the operational data is normally never captured and prepared for data mining purpose. Data in the real world is dirty because generally the data is captured from several inconsistent ,poorly documented operational systems. Real world data is often incomplete and noisy say wrong values or duplicate records. This results in poor quality data which in turn results in poor quality mining results. So ,many organizations or company are interested in how to transform the data into cleaned forms which can be used for high profit purposes. This goal generates an urgent need for data preprocessing. In this paper first, we show the importance of data preprocessing in data analysis ,then introduce some research achievements in the area of data preprocessing. finally we suggest some future direction and development
Keywords: Cleaning; Reduction; Transformation; Discretization; Concept Hierarchy